CREATION OF HIGH-PERFORMANCE DIAMOND BITS FOR EXPLORATION DRILLING IN HARD ROCKS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The accelerated commissioning of minerals occurring in hard rocks largely depends on the productivity of exploration drilling, the technical and economic indicators of which are largely determined by the efficiency of diamond drill bits.To solve the above problem, studies have been carried out that allow us to formulate the following recommendations for the creation of high-performance diamond bits for drilling hard abrasive rocks:the crown matrix should contain several (five or more) impregnated diamond-bearing layers in height, separated by diamond-free layers of significantly lower hardness (for example, VK-20 hard alloy);each diamond impregnated layer of the matrix must have a «comb» profile, representing annular wedge-shaped protrusions and depressions;the impregnated diamond layers of the matrix during drilling should be equally loaded along the radius of the bit, which makes it possible to increase the wear resistance of the tool and reduce the amount of rough diamonds for the manufacture of the latter; a dependence was obtained that determines the change in the height of the conical annular protrusions of diamond-containing layers in the direction from the peripheral protrusion to the axis of the crown, provided that the bases of the mentioned protrusions are equal;to maintain the diameters of the well and the drilled core, the inner and outer side surfaces of the matrix must be equipped with wear-resistant diamond inserts (for example, from tessal);to produce a high-quality wear-resistant matrix, small amounts of various components should be added to the composition of the binder of diamond grains of the 94WC + Co + Cu type; for example, it has been experimentally proven that the addition of tungsten monocarbide powder WC at a grain size of 200/160 increases the efficiency index by 1.9 times; the mentioned indicator is directly proportional to the mechanical drilling speed, the size of the well penetration and is inversely proportional to the linear wear of the matrix in height;to increase the intensification of the destruction of the bottom of the well, it is necessary to carry out experimental work with a diamond crown, the impregnated layers of which are placed in a matrix on a three-start helical surface with a small pitch of 0.8 - 1.2 mm; It is expected that with such a design, in addition to the depth of penetration of diamond grains, the process will involve a pre-fracture zone that lies under the zone of penetration and represents a hard rock broken and weakened by cracks to a depth that tenfold increases the depth of penetration of diamond grains.The above recommendations are embodied in the design of diamond impregnated crowns, for which patents of the Republic of Kazakhstan have been received. The crowns made according to recommendations 1-4 have been introduced into production with a significant effect when they are equipped with projectiles with removable core receivers (PRC).
Keywords: drill bit, multilayer matrix, impregnated and diamond-free layers, «comb» profile, wear resistance, addition of components, matrix bond, equally loaded profile.